Knowledge and Awareness about Importance of Aesthetics in Dentistry - S Sneka1 , Keerthi Sasanka2 , Gayatri Devi R3 , Visalakshi Ramanadhan4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Esthetic dentistry can be defined as the art and science of dentistry applied to create or enhance beautyof an individual within functional and physiological limits. Esthetics is the branch of philosophy dealingwith beauty. In dentistry, The theory and philosophy that deal with beauty1 and the beautiful, especiallywith respect to the appearance of a dental restoration, as achieved through its form of colour. The aim ofthis study is to assess the dental esthetics awareness among dental students. Survey was conducted online.Questionnaire which consists of 10 questions was prepared and distributed through google forms. Studypopulation consists of 100 dental students. This creates awareness about aesthetics and helps to understandthe importance of aesthetics and also provide required technology. This studies shows a high level of selfconsciousness and the findings of the studies prove that even slight variations have greater impact onphysiological functional and physical aspects.